WRITTEN PEER FEEDBACK IN VOCATIONAL SCHOOL (RETAIN, 2014)
WRITTEN PEER FEEDBACK IN VOCATIONAL SCHOOL Hidayatul Muniroh English Department, Language and Arts Faculty, State University of Surabaya Hidayatulmuniroh4@gmail.com Ahmad Munir English Department, Language and Arts Faculty, State University of Surabaya Munstkip@yahoo.com Abstract The present study aims to analyze what do the vocational students’ do to give written peer feedback and what they do to respond the peer feedback and the aspect that they evaluate in giving written peer feedback. This study is descriptive qualitative. The eleventh graders of SMK PRAPANCA 2 Surabaya are the subjects of the study. The main data was taken from the students’ writing personal letter. The data was gained through field note and analyzing the students’ writing. It was found that most of the students give feedback by giving signs (circling, underlining, crossing) and symbols without showing what errors made by the writer or giving the correctness. There were 7 students from 30 students who correcting and giving symbols to their peer’s writing. The aspects of writing that evaluated by the students were only the surface aspects of writing, such as; Grammar, vocabulary, spelling, and mechanic. They tended to ignore the content and unity of the sentences. It can be concluded that the implementation of written peer feedback in SMK PRAPANCA2 Surabaya was not applied well, because of the teacher misunderstanding. The teacher still confused about the differences between peer assessment and peer feedback Keywords: written peer feedback, vocational school, and peer assessment. Abstrak Penelitian ini bertujuan untuk menganalisis apa yang dilakukan oleh siswa SMK ketika memberikan respon tertulis dan aspek penulisan apa sajakah yang mereka evaluasi ketika mereka memberikan respon tertulis. Penelitian ini adalah deskriptif kualitatif. Subjek dari penelitian ini adalah siswa kelas XI SMK2 Prapanca Surabaya. Data utama dari penelitian ini adalah tulisan surat pribadi siswa. Dalam penelitian ini di temukan bahwa sebagian besar siswa memberi respon tertulis dengan memberikan tanda (menggaris bawahi, melingkari, dan mencoret) dan simbol-simbol tanpda menunjukan kesalahan yang dibuat oleh penulis tau memberikan pembenaran pada kesalahan. Dari 30 siswa hanya 7 diantaranya yang membenarkan dan memberikan simbol-simbol kepada tulisan pasangannya. Aspek penulisan yang dievaluasiole siswa hanyalah aspek dasar dari penulisan, antara lain; tata bahasa, kosa kata, pengejaaan, dan tanda baca. Dari penjalasan di atas, dapat disimpulkan bahwa penerapan respon tertulis berpasangan di SMK Prapanca2 tidak teraplikasikan dengan baik, karena salah pemahaman dari guru. Guru yang menerapkan teknik tersebut masih bingung dengan perbedaan antara pemberian nilai berpasangan (peer assessment) dan pemberian respon berpasangan (peer feedback). Kata kunci: Pemberian respon tertulis berpasangan, SMK, dan Pemberian nilai berpasangan. Introduction Byrne (1980) defines writing as a primary means of recording speech, even though it must be acknowledged as a secondary medium of communication. From that statement, it can be concluded that writing is very important as a media of communication that can help to express idea, feeling, and opinion to interact with the society. Specific writing assignment of writing in EFL for senior high school level not only conducted in senior high school (SMA) which learn more about writing some genre of writing, but also in vocational school (SMK). It is stated clearly in one of standard competency for vocational school that is the student must be able to write. One of them is the student should be able to write a personal letter which is telling about past events and planning for the future correctly, so the students should be able to master writing skill for particular purpose. It can be concluded that not only senior high school students that should be master in writing, but also vocational students. Students’ errors in writing cannot be avoided, because they are in progress of learning a foreign language in context. It should be considered as a natural process. The process of becoming a writer is an accumulation of knowledge and experiences that builds over time. To minimalize and improve the errors made by the students, the teacher should has a good way to make the students realize with the errors that they made, that is by letting the students giving and getting feedback in their writing by themselves. McGrath, Taylor, and Pychyl (2011) define feedback as a technique used by course instructors to communicate to students about their writing. Freedman (1987) states that feedback includes all reaction to writing, formal or informal, written or oral, from teacher or peer, to a draft or final version. One kind of feedback that can be used in the writing class is peer feedback. Peer feedback can be defined as an activity frequently used in second/subsequent (L2) writing classrooms to elicit feedback from a sympathetic reader, another student writer, on a draft version of a text. In the process, student writers receive feedback from peer readers, which gives the writers a sense of how readers might react to their texts. Peer written feedback can give advantages to the students. It benefits not only the students who receive suggestions for improving the writing, but also the feedback providers, as they gain a greater awareness of qualities of good writing through assessing and commenting on peers’ writing. Peer feedback also develops students’ self-assessment abilities, as they gain experience in using the criteria to read their own writing (Cho & MacArthur, 2010; Lundstrom & Baker, 2009). A substantial amount of research has been done over the years into the value of different kinds of feedback to student writers. Many studies typically focused either on teacher or peer feedback, or compared both and either looked at their effect on students’ ability in writing. For example, Yanuarseh (2013) reported the implementation of peer response technique in teaching writing on eleventh graders of senior high school was an appropriate technique in teaching and learning especially in writing hortatory exposition, because it can increase the student writing ability. Kilarskah (2008) demonstrated the results of a study involving second-year students of English Philology at The State Higher Vocational School in Nysa, Poland. In their writing class, students accustomed to the product-oriented writing instruction were introduced to the process approach by completing a cycle of three multiple-draft assignments. Students’ drafts in all three assignments were analyzed to determine how their papers changed in quality over time and if the feedback the students received from one another contributed to possible improvement. The result showed that the assignments did not contribute to significant improvement in the students’ composing skills. Yet, there has been no study which examines what vocational school students do to give peer feedback and what they do to respond it and what aspect of writing that they evaluate in giving written peer feedback in vocational school. This study was meant to fill in this gap. Methods This study was descriptive-qualitative. It was designed to know the students attitudes toward written peer feedback during the writing class. Ary, Jacobs, and Sorensen (2010) state qualitative researchers seek to understand a phenomenon by focusing on the total picture rather than breaking it down into variables, so the researcher investigate and observe what really happen in the field and reported what they are. Therefore, it took particular setting under the study and concern with context. Eleventh graders of vocational school of SMK Prapanca 2 Surabaya were the participant of this study. It was based on the consideration that they already have enough comprehensive in writing skills and understanding about peer writing feedback. Moreover, they also need to improve their writing skills because they have in high level of education. For the sample of this study, the researcher took a class which the teacher has implemented peer writing feedback before, that is XI AK-1 (accountant class) but it took only four students as the sample of this inquiry. They were fairly homogenous for the same mother tongue and education level, almost the same age, intelligence according to their teacher and they have learned the same material during their teaching learning process. The data that was used for this inquiry was taken from the students’ writing personal letter. The data was collected through the following steps; the first step was observing what vocational school students’ do to give written peer feedback and what they do to respond the peer feedback. It was gained through observation using field note during the teaching learning process. The second step was reading and analyzing the aspects of writing that the vocational students’ evaluate in giving written peer feedback. It was gained through reading and analyzing their writing personal letter and it was collected by copying their essay (documentary). It was conducted in the second meeting of observation after the essay was given back by the teacher to them. The researcher analyzed the data that was gained through the observation in descriptive qualitative way. The obtained data from the documentary and field note were analyzed based on the fact and interpretation noted down by the researcher during the teaching and learning process. To answer the research questions number one and two, the researcher used the following table: Table. 1 Student’s errors and category of feedback given by the students. Results and Discussion What vocational school students’ do to give written peer feedback and what they do to respond the peer feedback. The students gave feedback to their partners by correcting and giving some signs to the errors, such as; circling, crossing, giving questions mark, and underlining. However, there were only seven students from thirty students who were correcting the errors made by their partner. Table. 1 Student’s errors and category of feedback given by the students. From Table 1 it can be seen that from 30 students only 7 students who were correcting and giving symbols in their partner’s error. Most of students gave feedback to their partners’ writing by giving some signs or symbols without giving the correct one, for example: the students only gave underline in ungrammatical sentence, circle in incorrect spelling, and crossing in the wrong word. Here was a student’s writing personal letter which showed what vocational students did when giving feedback. Figure 1 Student 10’s writing personal letter; correcting and giving sign to the errors. From the Figure 1 it can be seen that the student number 10 gave feedback by correcting and giving signs to the errors. She corrected and circled the errors. She circled the wrong word “said” and gave the correct word “Sad”. After that, she also circled the word “in” because it was not appropriate there. However, she just circled an unclear sentence there without giving the correction. However, there were feedbacks which mean no feedback. It means that, the reviser gave feedback by underlining, crossing, and circling the errors but he/she did not give the feedback or correction to the errors. Here was the example of the student’s writing personal letter which consisted of feedback which means no feedback. Figure 2 the sudent 15’s writing personal letter From the Figure 2 above, student writing personal letter number 15 got feedback from the reviser, but no feedback. It means the reviser did not give the correction. For example in the word “a prolonged state scatheless” the reviser did not know the meaning of the sentence because it was not clear, but the reviser did not give any contribution of the errors. What vocational school students’ do to give written peer feedback and what they do to respond the peer feedback was not in line with Winne and Butler (1994) who provided that feedback is information with which a learner can confirm, add to, overwrite, tune, or restructure information in memory. Feedback is to be written then the extent of oral negotiation to clarify the feedback involve both the reader and writer, and the range of specific and persuasive feedback which given by the student-readers need to be considered (Rollinson, 2005:27). Aspects of writing After analyzing thirty students’ writing personal letter, the researcher found only seven writing personal letter which include the students’ feedback. From Tables 1 above, it could be seen that most of the students did the same errors in writing, such as; grammar, word choices, unclear sentences, and spelling. Here was a students’ writing personal letter which showed the aspects of writing which evaluated by the student. Figure 3 Student 11’s writing personal letter From the Figure 3 above, it could be seen that the student give feedback in some aspects of writing, such as; vocabulary, tenses, spelling, and unclear sentences. Student errors in spelling: in this case, the reviser circled the word “again” then she replaced it with “againd”. Student errors in grammar: in this case, the reviser just underlined the errors without giving the correction. I’m will to see you now à it should be “I will see you soon”, When go to in surabaya with mom and dad you? à it should be “ when will you go to Surabaya with your parents. Student errors in term of unclear sentence: in this case, the reviser gave feedback by giving question marks on the top of the sentence and underlined it. Figure 4 Unclear sentences and student’s error in word choice From the Figure 4 above, the student gave feedback by underlining the unclear sentences and giving question mark; for example; - In the sentence “while up to do for you”, the reviser did not know what the writer was meant. In this case the reviser gave feedback by underlining the sentence and question mark on it. Student’s error in term of word choices: in this case, the reviser gave feedback by giving question marks on the top of the sentence and underlined it. - Me and my family in a prolonged state scatheless à in this case the student choose difficult word and cannot be understood by the reader. From the discussion above, it could be concluded that the reviser looked the surface errors of the writing, because she just looked at the word choice, tenses, spelling, and punctuation. She did not paid attention on the content of the writing, the unity and coherent, and the organization. The aspects of writing which were evaluated by the students was in line with the theory of Brown (2001) which mentions five elements such as; content, organization, punctuation, vocabulary, and language use, but it was not exactly the same because in the content, the students’ just correct the unclear sentence made by the writer without giving correction. Conclusions From the results and discussions, it can be drawn two conclusion of this study. There were only seven students from thirty students who did written peer feedback by correcting and giving signs and symbols in their partners’ writing. Furthermore, most of the students give feedback by giving signs (circling, underlining, and crossing) and symbols without showing what errors made by the writer or giving the correctness. The aspects of grammar that evaluated by the students were only the surface aspects of writing, such as; Grammar, vocabulary, spelling, and mechanic. They tended to ignore the content and unity of the sentences. Overall, written peer feedback in SMK PRAPANCA Surabaya was not implemented well, because of the teacher misunderstanding. The teacher still confused about the differences between peer assessment and peer feedback. References Ary, D., Jacobs, L. C., & Sorensen, C. (2010). Introduction to Research in Education (8 ed.). Wadsworth: Cengage. Brown, H. D. 2001. Teaching by Principles. An Interactive Approach to Language Pedagogy. Second Edition. White Plain, N.Y: Pearson Education, Inc. Byrne, D. (1988). Teaching Writing Skills. London: Longman. Cho, K. & MacArthur, C. (2010). Student revision with peer and expert reviewing. Learning and Instruction, 20, 328-338. Freedman, S.W. (1987): Recent developments in writing: how teachers manage response. English Journal, 7, 35-40. Kilarska, Magdalen. (2008). Introducing Multiple-Draft Assignments in the Writing Classroom. The State Higher Vocational School, Nysa, Poland, 1-7. Lundstrom, K., & Baker, W. (2009). To give is better than to receive: The benefits of peer review to the reviewer’s own writing. Journal of Second Language Writing, 18, 30–43. McGrath, A. L., Taylor, A., & Pychyl, T. A. (2011). Writing Helpful Feedback: The Influence of Feedback Type on Students’ Perceptions and Writing Performance. The Canadian Journal for the Scholarship of Teaching and learning, 2(2), 1-16. Rollinson, P. (2005). Using peer feedback in the ESLwriting class. ELT Journal, 59(1), 23-30. doi: 10.1093/elt/cci003. Winne, P. H., & Butler, D. L. (1994). Student cognition in learning from teaching. In T. Husen & T. Postlewaite (Eds.), International encyclopaedia of education. 2nded. 5738-5745. Oxford, UK: Pergamon. Yanuarseh, Denny. (2013). The Effect of Using Peer Responseto Teach Writing Hortatory Exposition Text in Eleventh Graders of Senior High School (Unpublished S-1 Skripsi). State Universitiy of Surabaya. Advisor: Esti Kurniasih, S.Pd., M.Pd.